AN ASSESSMENT ON FISHERS’ COMPLIANCE BEHAVIOR IN PEMALANG REGENCY, CENTRAL JAVA - INDONESIA - Indah Susilowati (JOURNAL OF COASTAL DEVELOPMENT, 2003)
The study was conducted due to high incidence of non-compliance by fishers in Central Java fisheries. The overall objective of the study is to examine the compliance behavior of fishers in Pemalang Regency. Eighty-five (n=85) respondents have been selected from the study areas using multi-stages sampling method. Moreover, key-persons from Fisheries Office, Navy and head of fishers’ association have also been interviewed to enrich the analysis of the study. Non-compliance behaviour of fishers in this study was viewed from violation of: restricted area (zoning), restricted gears and means (explosive and poison) and administration (such as permits). Model of non-compliance behavior as outlined by Kuperan (1993) and Susilowati (1998) has been applied to analyze the data in this study with necessary modification. Tobit model explained by Gujarati (2003) was employed as the estimation techniques. Most of independent variables such as demographical factors, fishing effort, deterrence indicators and legitimacy variables have expected signs although statistically are not always significant. In general, the model of non-compliance behaviour could portrait the phenomena of violation behaviour of fishers in the study area. It is realized that law enforcement in Indonesian fisheries is weak for several reasons. Therefore, to improve the fishers’ compliance perhaps an alternative approach such as empowering the people and its stakeholders should be found.